2011
DOI: 10.1016/j.neuroimage.2010.09.040
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of [11C]MRB for assessment of occupancy of norepinephrine transporters: Studies with atomoxetine in non-human primates

Abstract: [11C]MRB is one of the most promising radioligands used to measure brain norepinephrine transporters (NET) with positron emission tomography (PET). The objective of this study was to evaluate the suitability of [11C]MRB for drug occupancy studies of NET using atomoxetine (ATX), a NET uptake inhibitor used in the treatment of depression and attention-deficit hyperactivity disorder (ADHD). A second goal of the study was identification of a suitable reference region. Ten PET studies were performed in three anesth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 39 publications
(67 reference statements)
3
44
0
1
Order By: Relevance
“…This is consistent with the known distribution of the NET in brain. 17,21 This PET tracer has been shown to be useful in NET occupancy studies 22,23 of atomoxetine hydrochloride and methylphenidate, which have demonstrated its use in measuring NET availability in vivo.…”
mentioning
confidence: 99%
“…This is consistent with the known distribution of the NET in brain. 17,21 This PET tracer has been shown to be useful in NET occupancy studies 22,23 of atomoxetine hydrochloride and methylphenidate, which have demonstrated its use in measuring NET availability in vivo.…”
mentioning
confidence: 99%
“…Thus correction for the free fraction of parent in plasma may be critical for accurate quantification of [ 18 F]DBT-10. The use of V T / f P as a more stable outcome measure than V T has been previously reported for PET radioligands in other neurotransmitter systems [26]. Importantly, the [ 18 F]DBT-10 f P values, ranging from 15–22% at baseline, are sufficiently large for reliable measurement, thus the need to correct for f P should not impede the accurate quantification of [ 18 F]DBT-10 binding.…”
Section: Discussionmentioning
confidence: 92%
“…ATX is a selective pre-synaptic NET blocker affecting NE and DA in the prefrontal cortex (Bymaster et al 2002) and NE in the thalamus, locus coeruleus and cerebellum, with minimal striatal effects (Gallezot et al 2011).…”
Section: Introductionmentioning
confidence: 99%